Implementasi Hak Akses User dalam Mencegah Kebocoran Data Jaringan - Intan Sahyuni; Aura Chintiya Bella; Muhammad Rijal; Syaira Ramadhani; Eksyel Bongga Upa’; Suci Dian Azzahra; Ketrin Rinayanti Manullang (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Network security has become an important issue in the digital era due to the increasing use of data-based systems in various sectors. Many organizations store important information within computer networks, causing the risk of data leakage to increase significantly. One of the main causes of data leakage is poor user access management. This study aims to analyze the implementation of user access rights in preventing network data leakage through the application of Role-Based Access Control (RBAC) and Network Access Control (NAC). The research method used is a quantitative approach with descriptive-analytical methods and network system simulations. Research data were obtained through user access testing and network activity analysis. The results show that the implementation of RBAC can limit user access according to their duties and responsibilities, thereby reducing the risk of data misuse. In addition, the use of NAC helps the system validate devices that are allowed to access the network. The combination of these two methods has proven effective in improving network security and reducing the risk of data leakage significantly.